2023
DOI: 10.1097/pap.0000000000000399
|View full text |Cite
|
Sign up to set email alerts
|

Pericardial Mesotheliomas

Abstract: Primary pericardial mesothelioma (PM) is a rare tumor arising from the mesothelial cells of the pericardium. It has an incidence of <0.05% and comprises <2% of all mesotheliomas; however, it is the most common primary malignancy of the pericardium. PM should be distinguished from secondary involvement by the spread of pleural mesothelioma or metastases, which are more common. Although data are controversial, the association between asbestos exposure and PM is less documented than that with other mesotheliomas.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…This choice was made based on the patient's preference for palliative chemotherapy over surgical intervention following a full discussion of treatment plans. Due to its rarity, there is no consensus on the treatment of PPM ( 1 , 2 , 5 , 6 ). Currently, treatment options for PPM are adapted from the more often studied diffuse pleural mesotheliomas ( 1 , 2 , 18 ); surgery is the most widely-used approach, followed by chemotherapy ( 5 , 6 , 18 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This choice was made based on the patient's preference for palliative chemotherapy over surgical intervention following a full discussion of treatment plans. Due to its rarity, there is no consensus on the treatment of PPM ( 1 , 2 , 5 , 6 ). Currently, treatment options for PPM are adapted from the more often studied diffuse pleural mesotheliomas ( 1 , 2 , 18 ); surgery is the most widely-used approach, followed by chemotherapy ( 5 , 6 , 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Due to its rarity, there is no consensus on the treatment of PPM ( 1 , 2 , 5 , 6 ). Currently, treatment options for PPM are adapted from the more often studied diffuse pleural mesotheliomas ( 1 , 2 , 18 ); surgery is the most widely-used approach, followed by chemotherapy ( 5 , 6 , 18 ). However, in a review of 103 published PPM cases, it was found that chemotherapy, but not surgery, provided a statistically significant survival benefit.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations